2020
DOI: 10.1177/2041386620962569
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the social identity theory of leadership: A meta-analytic review of leader group prototypicality

Abstract: This research advances a social identity approach to leadership through a meta-analysis examining four novel hypotheses that clarify the nature and impact of leader group prototypicality (the extent to which a leader is perceived to embody shared social identity). A random-effects meta-analysis ( k = 128, N = 32,834) reveals a moderate-to-large effect of prototypicality that holds across evaluative and behavioral outcomes. The effect is stronger (a) when prototypicality is conceptualized as the ideal-type rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 155 publications
7
137
0
4
Order By: Relevance
“…According to the social identity approach to leadership (Hogg, 2001;van Knippenberg & Hogg, 2003), the effectiveness of leadership depends on a sense of shared group membership between leader and followers (i.e., "we-ness"). Studies have shown that ingroup identifiers would consider a leader to be influential, effective, and trustworthy if they perceive this leader to be prototypical of the group (i.e., representing the group; e.g., Giessner & van Knippenberg, 2008; for a meta-analysis, see Steffens, Munt, van Knippenberg, Platow, & Haslam, 2021).…”
Section: Predictions For the United Statesmentioning
confidence: 99%
“…According to the social identity approach to leadership (Hogg, 2001;van Knippenberg & Hogg, 2003), the effectiveness of leadership depends on a sense of shared group membership between leader and followers (i.e., "we-ness"). Studies have shown that ingroup identifiers would consider a leader to be influential, effective, and trustworthy if they perceive this leader to be prototypical of the group (i.e., representing the group; e.g., Giessner & van Knippenberg, 2008; for a meta-analysis, see Steffens, Munt, van Knippenberg, Platow, & Haslam, 2021).…”
Section: Predictions For the United Statesmentioning
confidence: 99%
“…Identity prototypicality refers to the notion of being one of us (Haslam et al, 2011;Steffens, Haslam, Reicher, et al, 2014). Ample of evidence underscores the importance of leaders to be seen as one of us (rather than one of them) and representing what makes us special (Barreto & Hogg, 2017;Steffens et al, 2021;van Knippenberg, 2011). Identity advancement refers to the notion of doing it for us (Haslam et al, 2011;Steffens, Haslam, Reicher, et al, 2014).…”
Section: Identity Leadership and Burnoutmentioning
confidence: 99%
“…Firstly, our research contributes to the social identity approach of the leadership literature. Prior research has focused on the influence of leader identity prototypicality on employees and group outcomes or viewing leader identity prototypicality as a boundary condition that moderates the effectiveness of leadership behaviors (e.g., van Knippenberg, 2011;Steffens et al, 2021), ignoring the effect of identity leadership as a higher-order construct. As noted by van Dick et al (2018), a full scale with four dimensions allows researchers to better capture the richness of identity leadership.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Although a social identity approach of leadership has attracted considerable attention from researchers in the past two decades, most previous studies focus on theoretical articulation and the single dimension of leader identity prototypicality (Steffens et al, 2014). In this regard, existing empirical evidence has suggested that leader identity prototypicality contributes to leadership effectiveness (van Knippenberg, 2011;Steffens et al, 2021). However, other equally significant aspects of identity leadership are neglected (Steffens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%